ANALISA DEBIT RENCANA BENDUNG JANGKOK: Discharge Analysis of The Jangkok Dam Plan - Sujendra, I Nengah Eka; Yamin, Muhamad; Aminullah, Aminullah (Yayasan Al-Amin Qalbu, 2024)
The purpose of this research is to know the value of PMP (Probable Maximum Precipitation), to analyze the design flood discharge to evaluate the magnitude of the design flood discharge at various return periods of 2, 5, 10, 20, 25, 50, 100 years, to analyze the peak discharge, peak time and time basis using the Snyder Synthetic Unit Hydrograph. In this research conducted in the Jangkok Watershed (DAS), West Lombok Regency, the type of data used in this study was data obtained from secondary data, literature studies, various literature, as well as observational and measurement data at the research location. The annual maximum rainfall is 121.78 mm while the average rainfall is 12.178 mm, the PMP (Probable Maximum Precipitation) value on the Jangkok river is 79.563 mm, the design flood seed with a return period of 2, 5, 10, 20, 25, 50, and 100 years using the Haspers method obtained respectively: 126.70 mm; 292.11 mm, 584.23 mm, 1168.47 mm, 1460.58 mm, 2921.17 mm, 5842.35 mm, peak time (Tp), peak discharge (Qp) and base time (Tb) after calculations using the developed Snyder HSS method are obtained for: Tp = 0.538 hours; Qp = 147.364 m3 and Tb = 0.059 hours.